Métodos de controle de qualidade aplicados a produtos cosméticos baseados em nanotecnologia - João, Luana (Universidade Federal de São Carlos, 2025)
Driven by consumers who are increasingly concerned with physical appearance, the cosmetics market has grown significantly in Brazil and around the world in recent years. According to data from Euromonitor International, Brazil ranks third in the global market for cosmetics and personal care products. However, alongside the growth of this sector, the public has become increasingly demanding, seeking products that not only offer traditional functions such as hydration, cleansing, and exfoliation, but also provide personalized benefits and care tailored to individual needs. This includes products that help reduce sunspots, acne, oiliness, rosacea, and more. In order to meet these consumer demands, the cosmetics industry has been investing in the development of new technologies aimed at enhancing the performance of active ingredients. Among these innovations, nanotechnology has stood out. It enables the development of cosmetic-grade materials at the nanometric scale typically between 1 to 100 nanometers which, due to their size and characteristics such as charge and surface area, exhibit unique properties that enhance their effectiveness in cosmetic formulations. Because of their reduced size, nanostructured materials used in these products present an increased surface area, which directly impacts their chemical reactivity, as well as quantum effects that significantly modify their optical and magnetic properties, for example. As a result, the application of nanotechnology in beauty products not only enhances the activity of the actives but also improves their stability, release, and skin absorption, thereby increasing the product's overall efficacy. However, before reaching consumers, cosmetic and personal care products must undergo a series of quality control tests to ensure their safety and effectiveness. These include physicochemical, organoleptic, and analytical tests. In Brazil, ANVISA is the agency responsible for the regulation of cosmetics and personal care products. Meanwhile, the FDA and the European Union provide guidance on the safety of nanomaterials used in cosmetic formulations. Therefore, this undergraduate thesis aims to present the quality control methods for cosmetic products containing active ingredients at the nanometric scale.
Quality control methods applied to cosmetic products based on nanotechnology
Keywords: Cosméticos; Nanotecnologia; Controle de qualidade cosmética; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA